Workshop Penggunaan Media Interaktif Pembelajaran Terkini Bagi Para Guru Ppmi Shohwatul Isad - Yusring Sanusi Baso (Khazanah Pengabdian, 2020)
This activity is intended to share learning methods, specifically the use of interactive learning media. Some of the activities have been carried out at the first visit of the Arabic Literature study program team represented by Yusring Sanusi B to PPMI Shohwatul Is'ad. During this visit the activities that will be carried out at this workshop are discussed. Furthermore, a subsequent visit was conducted in a workshop for teachers PPMI Shohwatul Isad. The last visit was attended by all team members and students. During this last visit, there was a material change. The teachers asked to be given learning techniques with paper media. It is hoped that this learning model can be adapted creatively by the teachers of PPMI Shohwatul Is'ad. This activity has been recorded in order to be seen and watched at anytime in how to engage students in the classroom with minimal media. Although this last activity is not related to computer technology, it does not reduce the main purpose of this service. The final visit was only verification of the CD that have been made by the teachers. The results of this service are interactive exercise CDs prepared by teachers, expecially for English, Indonesian, Mathematics, Biology and Physics.